2013
DOI: 10.1080/02701960.2013.809714
|View full text |Cite
|
Sign up to set email alerts
|

Positioning Medical Students for the Geriatric Imperative: Using Geriatrics to Effectively Teach Medicine

Abstract: Medical schools must consider innovative ways to ensure that graduates are prepared to care for the aging population. One way is to offer a geriatrics clerkship as an option for the fulfillment of a medical school's internal medicine rotation requirement. The authors' purpose was to evaluate the geriatrics clerkship's impact on internal medicine knowledge and medical student attitudes toward older adults. Mean National Board of Medical Examiners (NBME) internal medicine subject exam scores from geriatrics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In the present experiment, the authors examined whether viewing a pain-focused documentary could affect the perception of older adults and their many medical struggles among college students, with the intent of improving empathy and attitude towards them. Similar to previous research on the impact of exposure on empathy, 13 , 24 27 , 30 32 , 35 the significant between Group and Time found in the Profile Analysis results indicated that viewing the pain documentary did in fact impact experimental participants’ empathy scores positively and significantly. Follow-up t -test analyses were performed in order to delineate this effect; it was discovered that the impact of viewing the pain documentary was reflected in the significant changes in participants’ empathy scores, and this effect was only found in the experimental group.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the present experiment, the authors examined whether viewing a pain-focused documentary could affect the perception of older adults and their many medical struggles among college students, with the intent of improving empathy and attitude towards them. Similar to previous research on the impact of exposure on empathy, 13 , 24 27 , 30 32 , 35 the significant between Group and Time found in the Profile Analysis results indicated that viewing the pain documentary did in fact impact experimental participants’ empathy scores positively and significantly. Follow-up t -test analyses were performed in order to delineate this effect; it was discovered that the impact of viewing the pain documentary was reflected in the significant changes in participants’ empathy scores, and this effect was only found in the experimental group.…”
Section: Discussionsupporting
confidence: 85%
“… 29 In this regard, medical students who completed a geriatric clerkship as part of their internal medicine rotation reported a more positive attitude towards older adults. 30 Furthermore, in two investigations on this topic, Kumagai 31 , 32 used a story-telling approach to improve attitudes among medical students as students paid home visits to the family of a patient affected with chronic conditions during the two years of their program. After a scheduled home visit and listening to the volunteers’ life stories, students participated in small group discussions with their instructor in the first study; in the follow-up study on the effects of “diabetes stories”, students were asked to reflect on how their understanding of chronic illness differed from knowledge gained through lectures and textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…Geriatric clerkships can fulfil a medical school's internal medicine rotation requirement. A study found that examination proficiency was similar, while greater confidence in treating older adults and more positive attitudes towards older adults were found in the students completing a geriatric versus an internal medicine clerkship [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…As they hone their professional identities and are socialized into the profession, they will have to develop their own clinical judgments and relational styles, remain open to new clinical encounters and continue to grow professionally. Reflection that is encouraged by teachers and mentors helps this process (Goldie, 2012;Mann, 2011;Nguyen et al, 2013).…”
Section: Discussion and Recommendationsmentioning
confidence: 98%
“…Students' perspectives on professionalism develop with knowledge, methods and skills (Hilton & Slotnick, 2005;Wear & Castellani, 2000). Clinical mentorship in undergraduate medical education is an important component in fostering professionalism (Baernstein, Oelschlager, Chang, & Wenrich, 2009;Goldie, 2012), and educational interventions with older adults may help mitigate negative attitudes regarding the care of elderly patients (Bradley & Leipzig, 2013;Kalisch, Coughlin, Ballard, & Lamson, 2012;Nguyen, Duthie, Denson, Franco, & Duthie, 2013). Medical students' interactions with clinical mentors when caring for older adults may promote reflection on key aspects of developing professionalism, such as considering how their mentors handle challenging patient situations as well as considering geriatrics as a career choice .…”
Section: Introductionmentioning
confidence: 99%